Inovasi dalam Pengajaran Bahasa Arab: Menggunakan Aplikasi dan Platform Online untuk Pembelajaran Nahwu yang Lebih Menarik - Fara Suci; Moh. Syaifudin (Global Action and Education for Society, 2024)
Teaching Arabic, especially in the Nahwu (syntax) aspect, is often considered difficult and boring by students. With technological advances, online applications and platforms offer innovative solutions to address these challenges. This article explores how the use of applications and digital platforms can improve engagement and effectiveness in Nahwu learning. Using a qualitative approach through literature studies, surveys, observations, and interviews, the study finds that interactive features, flexible accessibility, learning personalization, and instant feedback from applications can enrich student learning experiences. However, there are challenges such as limited access to technology and teacher training needs that need to be addressed. With the right implementation strategy, technology can be an effective tool to create a more exciting and productive Nahwu learning experience.